Уточненный выбор допустимых сечений электрических проводов и кабелей в силовых цепях промышленного электрооборудования с учетом аварийных режимов работы - Баранов, Михаил Иванович (Национальный технический университет "Харьковский политехнический институт", 2019)
Приведены результаты разработанного инженерного электротехнического подхода к уточненному расчетному вы-бору предельно допустимых сеченийSil электрических не изолированных проводов, изолированных проводов и кабелей с поливинилхлоридной(ПВХ), резиновой (Р) и полиэтиленовой (ПЭТ) изоляцией и медными(алюминиевыми) жилами (оболочками) по условию их термической стойкости, по которым в силовых цепях электроустановок общепромыш-ленного назначения в аварийном режиме протекает токik(t) короткого замыкания (КЗ) с заданными параметрами. На основании этого подхода осуществлен уточненный выбор сечений Sil для указанных проводов(кабелей) силовых цепей исследуемого электрооборудования. Выполнена расчетная оценка предельно допустимых амплитуд плотностей δilm токаik(t) КЗ в рассматриваемых проводах и кабелях силовых цепей указанных электроустановок. Полученные результаты будут способствовать повышению термической стойкости электрических не изолированных проводов, изолированных проводов и кабелей с ПВХ, Р и ПЭТ изоляцией и медными(алюминиевыми) жилами(оболочками), широко применяемых в силовых цепях электроустановок общепромышленного назначения.

Implementation and clarification of the existing engi-neering approach for determination in industrial power engi-neering for allowable sectionsof cable-conductor products (CCP) Silof electric wires and cables inthe circuits of electrical equipment of the general industrial installations characterized flowing in malfunction of current ik(t) of short circuit (SC) with different amplitude-temporal parameters (ATPs). Methodology.Scientific and technical bases of electrical power engineering, electrophysics bases of technique of high voltage and high pulse currents, theoretical bases of the electrical engineering. Results.The results of the developed engineering approach are resulted in the calculation determination on the condition of thermal resistibility of CCP permissible sections of Silof the uninsulated wires, insulated wires and cableswith copper (aluminum) cores (shells), polyvinyl chloride (PVC), rubber (R) and polyethylene (PET) insulation, on which in malfunction of their operation the current ik(t) of SC can flow with the set by normative documents of ATP. It is shown that divergence between the values of basic calculation coefficient of Cikby existing and offered to the engi-neering calculations selection of permissible sections of Sil of cores (shells) of the tested wires and cables for normal of their operating time at the nominal current load of CCP makes no more (3-8) %, and in the mode of de-energizing of CCP arrives at to (9-26) %.. Analytical correlation is got for the specified cal-culation determination of integral of action of Jak of current ik(t) of SC (Joule integral) in the power circuits of the tested electrical equipment. It is set that in the circuits of of the general industrial installations (for permanent time of slump of Ta =20 ms of aperi-odic constituent of current of SC) maximum possible amplitudes of density of δilm≈Imk/Sil of SC current at time of his disconnecting tkC=100 ms for the uninsulated wires with copper (aluminum) cores make according to approximately 0.64 (0.36) кА/mm2, for cables with copper (aluminum) cores (shells), PVC and R insula-tion – 0.47 (0.30) кА/mm2, and for cables with copper (aluminum) cores ( shells) and PET insulation – 0.39 (0.25) кА/mm2. At time of disconnecting tkC=160 ms of SC current in the circuits of electrical equipment (Ta=20 ms) permissible amplitudes of cur-rent density of δilm of SC for the unsuolated wires with copper and aluminum cores are accordingly about 0.52 (0.29) кА/mm2, for cables with copper (aluminum) cores (shells), PVC and R insu-lation of 0.39 (0.25) кА/mm2, and for cables with copper (alumi-num) cores (shells) and PET insulation – 0.32 (0.21) кА/mm2. Originality.First by a calculation the specified numeral values of sections of Sil and amplitudes of density δilm of SC current are determined for the uninsulated wires, insulated wires and cables with copper (aluminum)cores shells), PVC, R and PET insula-tion. New analytical correlation is offered for the calculation estimation of thermal resistibility of tested CCP to the action of current of SC. Practical value.The obtained results will be use-ful in the increase of thermal resistibility of CCP with copper (aluminum) cores (shells), PVC, R and PET insulation, widely applied in the power circuits of electrical equipment of the gen-eral purpose industrial installations.
Refined selection of allowable cross-sections of electrical con-ductors and cables in the power circuits of industrial electrical equipment taking into account emergency operating modes
Keywords: электроэнергетика; расчетный выбор предельно допустимых сечений проводов и кабелей в цепях электрооборудования; electric power engineering; calculation selection of allowable sections of wires and cables in the circuits of electrical equipment